The Dispensatory of Ibn at-Tilmīd̲̲̲ : Arabic text, English translation, study and glossaries - Ibn al-Tilmīdh, Hibat Allāh ibn Ṣāʻid, 1073 or 4-1164 or 5. (Islamic philosophy, theology and science, 2007)
This book offers a critical Arabic edition, annotated English translation, introductory study, and two-way glossaries of the famous dispensatory composed around the middle of the 12th century CE by the Nestorian physician Ibn at-Tilmīḏ. The dispensatory, recognized as a masterpiece already by mediaeval contemporaries, soon after its appearance became the pharmacological standard work in the hospitals and apothecs of Baghdad and the wider Arab East, replacing, after almost 300 years, the vademecum of Sābūr ibn Sahl. The dispensatory of Ibn at-Tilmiḏ marks the apogee and the conclusion of centuries of medico-pharmacological development in the Arab world, and it is therefore absolutely essential for a critical understanding of mediaeval Arabic medicine and pharmacy in particular, and premodern science in general.